Technical Efficiency Performance of Halal Food and Beverages Companies in Indonesia and Malaysia - Ramadhani, Indria; Katri, Fatin Salwa Binti Haji (Muslim Business and Economics Review, 2024)
Indonesia and Malaysia are among the top most influential countries globally for halal food and beverages (HF&B). As a result, there is a perception that these nations’ HF&B companies are mature enough to have robust operational and managerial systems. This leads to a question on how HF&B companies handle unprecedented events. This paper examines the efficiency of HF&B companies, proxied by technical efficiency (TE) score in Indonesia and Malaysia over a five year period – covering the pre-COVID-19 period (2018-2019) and during the pandemic (2020-2022) –using Stochastic Frontier Analysis. The findings indicate that Indonesia's HF&B perform better over the period by showing 60% TE, whereas Malaysia's was at 50%. Interestingly, Malaysia's TE slightly increased during the COVID outbreak, whereas Indonesia showed a reverse pattern, with decreasing TE during the first year of the pandemic. Furthermore, both countries’ HF&B require further improvement, as because between 40% and 50% of the production input is inefficient, which means the production outputs are not optimal for profit. The significant factors requiring improvement from industry players are managing the cash and inventory cycle, along with adding or upgrading any necessary fixed assets such as equipment to reach productivity at an optimum level. This findings also indicate the benchmark for the HF&B industry as well as the current stage for competitiveness among the countries.